The role of procalcitonin as a prognostic factor for acute cholangitis and infections in acute pancreatitis: a prospective cohort study from a European single center. Issue 6 (June 2022) - Alberti, Piero; Pando, Elizabeth; Mata, Rodrigo; Cirera, Arturo; Fernandes, Nair; Hidalgo, Nils; Gomez-Jurado, María J.; Vidal, Laura; Dopazo, Cristina; Blanco, Laia; Gómez, Concepción; Caralt, Mireia; et al.
Abstract: Background: Infection in acute pancreatitis will worsen the disease prognosis. The aim of our study was to analyze the role of procalcitonin as a prognostic biomarker for infections and clinical severity. Method: A prospective single-cohort observational study of patients diagnosed of acute pancreatitis (n = 152) was designed. PCT determination was tested on admission (first 72 h). Infections (biliary, extrapancreatic and infected pancreatic necrosis), need for antibiotics, urgent ERCP and severity scores for acute pancreatitis was assessed. ROC curves were designed and the area under the curve was calculated. Logistic regression for multivariate analysis was performed to evaluate the association between procalcitonin optimal cut-off level and major complications. Results: PCT >0.68 mg/dL had higher incidence of global infection, acute cholangitis, bacteraemia, infected pancreatic necrosis, use of antibiotics in general, and need for urgent ERCP. In the multivariate regressions analysis, PCT >0.68 mg/dL at admission demonstrated to be a strong risk factor for complications in acute pancreatitis. Discussion: PCT levels can be used as a reliable laboratory test to predict infections and the clinical severity of acute pancreatitis. High levels of PCT predict antibiotics prescription as well as the need for urgent ERCP in patients with concomitant clinically severe cholangitis.